2021
DOI: 10.1038/s43247-021-00192-w
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide fluxes increase from day to night across European streams

Abstract: Globally, inland waters emit over 2 Pg of carbon per year as carbon dioxide, of which the majority originates from streams and rivers. Despite the global significance of fluvial carbon dioxide emissions, little is known about their diel dynamics. Here we present a large-scale assessment of day- and night-time carbon dioxide fluxes at the water-air interface across 34 European streams. We directly measured fluxes four times between October 2016 and July 2017 using drifting chambers. Median fluxes are 1.4 and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 51 publications
6
19
1
Order By: Relevance
“…hypothesized the lower CO2 fluxes observed during the day (~18:00) were likely a result of elevated primary productivity during the afternoon, primarily in the summer months, but could have also been due to convective mixing in the water column at night. Altogether, our results provide additional evidence that the time of sample collection has important implications for upscaling freshwater GHG fluxes to longer timescales(Attermeyer et al 2021;Gómez-Gener et al 2021). A previous study conducted in FCR which estimated CO2 and CH4 diffusive fluxes using discrete GHG measurements collected at ~noon concluded FCR was often a small CO2 sink during the summer stratified period in(McClure et al 2018, whereas our diel EC data indicate that FCR was an overall CO2 source throughout the summer in both 2020 and 2021.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…hypothesized the lower CO2 fluxes observed during the day (~18:00) were likely a result of elevated primary productivity during the afternoon, primarily in the summer months, but could have also been due to convective mixing in the water column at night. Altogether, our results provide additional evidence that the time of sample collection has important implications for upscaling freshwater GHG fluxes to longer timescales(Attermeyer et al 2021;Gómez-Gener et al 2021). A previous study conducted in FCR which estimated CO2 and CH4 diffusive fluxes using discrete GHG measurements collected at ~noon concluded FCR was often a small CO2 sink during the summer stratified period in(McClure et al 2018, whereas our diel EC data indicate that FCR was an overall CO2 source throughout the summer in both 2020 and 2021.…”
supporting
confidence: 56%
“…Other studies, however, have observed more consistent diel patterns in GHG fluxes. For example, some studies have shown higher CH4 fluxes during the night in lakes and reservoirs (Eugster et al 2011;Podgrasjek et al 2014;Waldo et al 2021) and higher CO2 fluxes at night in streams (Attermeyer et al 2021;Gómez-Gener et al 2021). On the other hand, some studies observed higher CH4 fluxes during the day as compared to night (Erkkiliä et al 2018;Jammet et al 2017;Podgrasjek et al 2016;Sieczko, et al 2020).…”
Section: Variability In Sub-daily Fluxes With Higher Dawn Than Dusk C...mentioning
confidence: 99%
“…All CO 2 diffusive flux measurements in this study were carried out during the day, but in such productive lakes the nighttime activity may profoundly affect these fluxes and even reverse them. Nighttime emissions were found to exceed daytime CO 2 emissions in several freshwater systems (39% Attermeyer et al 2021, 27% Gómez‐Gener et al 2021, and 70% Liu et al 2016). If we apply a nighttime CO 2 correction factor obtained from the studies mentioned above (an average nighttime increase of 54.5 ± 21.9%) to our average area‐weighted diurnal CO 2 fluxes (−1.8 ± 0.6 and 4.4 ± 6.8 mmol m −2 d −1 for clear and turbid lakes, respectively), our average diurnal estimates would be in the order of −1.4 ± 0.7 and 5.4 ± 7.6 mmol m −2 d −1 for clear and turbid lakes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing maximum temperatures will additionally directly stress cold-water organisms (Réalis-Doyelle et al 2016 ; McCullough et al 2009 ). Given the importance of water temperature for the ecology or the metabolism of rivers (Woodward et al 2010 ; Attermeyer et al 2021 ), and the fact that temperatures are increasing rapidly worldwide (IPCC 2021 ), our findings of winter warming and increasing maximum/minimum temperatures are important to understand the thermal dynamics of mountain rivers and the consequences of climatic changes on river ecosystems in general.…”
Section: Discussionmentioning
confidence: 92%